Experiences and responses of second victims of patient safety incidents in Korea: a qualitative study - Won Lee; Jeehee Pyo; Seung Gyeong Jang; Ji Eun Choi; Minsu Ock (BMC Health Services Research, 2019)
Abstract Background Healthcare professionals who experience trauma due to patient safety incidents can be considered second victims, and they also suffer from various difficulties. In order to support second victims, it is necessary to determine the circumstances of the incidents in question, along with the symptoms that the victims are experiencing and the support they require. A qualitative study on healthcare professionals of various occupations, such as physicians and nurses working in Korea, was conducted, and the experiences and response methods and processes of second victims were examined. Methods In-depth interviews were conducted with 16 healthcare professionals (six physicians, eight nurses, and two pharmacists) who had experienced a patient safety incident. All interviews were recorded and transcribed, and the data analysis was conducted in accordance with Strauss and Corbin’s grounded theory. Both open coding and axial coding were performed. Consolidated criteria for reporting qualitative research (COREQ) were applied in this study. Results The results of the open coding demonstrated that the experiences of second victims can be categorized into “the reactions of the first victim and surrounding people after the incident,” “Influence of factors aside from the incident,” “the initial complex responses of the participants to the incident,” “open discussion of the incident,” “the culture in medical institutions regarding early-stage incident response,” “the coping responses of the participants after incidents,” and “living with the incident.” Then, the seven categories in the open coding stage were rearranged according to the paradigm model, and the reaction process of the second victims was analyzed through process analysis, being divided into the “entanglement stage,” “agitating stage,” “struggling stage,” “managing stage,” and “indurating stage.” Conclusions This research is significant because it provides a comprehensive understanding of second victims’ experiences in the eastern region of Korea, by obtaining data using a qualitative research method. The findings of the study also highlight the five stages of the second victim response process, and can be used to design a specialized second victim support program in Korea.